Aflatoxins in Uganda: An Encyclopedic Review of the Etiology, Epidemiology, Detection, Quantification, Exposure Assessment, Reduction, and Control - Timothy Omara; Winfred Nassazi; Tom Omute; Aburu Awath; Fortunate Laker; Raymond Kalukusu; Bashir Musau; Brenda Victoria Nakabuye; Sarah Kagoya; George Otim; Eddie Adupa (International Journal of Microbiology)
Uganda is an agrarian country where farming employs more than 60% of the population. Aflatoxins remain a scourge in the country, unprecedentedly reducing the nutritional and economic value of agricultural foods. This review was sought to synthetize the country’s major findings in relation to the mycotoxins’ etiology, epidemiology, detection, quantification, exposure assessment, control, and reduction in different matrices. Electronic results indicate that aflatoxins in Uganda are produced by Aspergillus flavus and A. parasiticus and have been reported in maize, sorghum, sesame, beans, sunflower, millet, peanuts, and cassava. The causes and proliferation of aflatoxigenic contamination of Ugandan foods have been largely due to poor pre-, peri-, and postharvest activities, poor government legislation, lack of awareness, and low levels of education among farmers, entrepreneurs, and consumers on this plague. Little diet diversity has exacerbated the risk of exposure to aflatoxins in Uganda because most of the staple foods are aflatoxin-prone. On the detection and control, these are still marginal, though some devoted scholars have devised and validated a sensitive portable device for on-site aflatoxin detection in maize and shown that starter cultures used for making some cereal-based beverages have the potential to bind aflatoxins. More efforts should be geared towards awareness creation and vaccination against hepatitis B and hepatitis A to reduce the risk of development of liver cancer among the populace.